PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN OTOMOTIF DAN KOMPONEN TERDAFTAR BEI PERIODE 2019-2022 - Noviadry Nur Tamtama; Rahmawati Riantisari (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
Growth in the quantity of motorized transport continues to increase every year. These conditions will certainly have an impact on the profitability of automotive and component companies. There are many studies studying the factors that impact profitability. This study focuses on capital structure and liquidity factors. This variable was chosen because it found various research results. The population of this study are automotive and component companies listed on the IDX. The research sample is a company that includes annual financial reports for the 2019-2022 period, namely 9 companies. The data collection method is through observation of financial data analysis which is then processed to see the results of DER, CR and ROA calculations. Analysis to test the correctness of the data using the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Testing the truth of the hypothesis using multiple regression test. The results of the study prove that capital structure has an effect on profitability. Liquidity has no impact on company profitability. Through the results of the research and discussion it is concluded that the capital structure has an impact on the profitability of the institution or institutions. Liquidity has no effect on institutional profitability. Through the results of a review of the suggestions provided, the institution should be more careful about the composition of the components of the capital structure. Key Words: Capital Structure, Liquidity, Profitability, Automotive and Components, IDX